Monitoring of the tritium concentration in the hydrographic network of the Belarusian NPP construction area - Zhuravkov, Vladzislav V.; Pazniak, Sergei S.; Skibinskaya, Anna N. (Journal of the Belarusian State University. Ecology, 2019)
The article presents the generalized data for determining the background levels of tritium in open water bodies in the area of the Belarusian NPP construction, conducted by the International Sakharov Environmental Institute of the Belarusian State University (ISEI BSU). The results were obtained on the basis of developed in the ISEI BSU the unique method for the determination of low tritium activities in water on the liquid-scintillation radiometers of the TRI-CARB and QUANTULUS series [1]. The work was carried out within the framework of the Research work: «Comprehensive environmental monitoring of the Belarusian NPP for the construction period (Determination of tritium content in surface and ground water samples) sponsored by Republican center for hydrometeorology, control of radioactive contamination and environmental monitoring. As a result of the work, the specific activity of tritium in open water bodies in the area of the Belarusian NPP construction was determined. At the same time, for the entire observation cycle, sixty-two surface water samples were taken at sites in the observation zone of the Belarusian NPP, more than 310 direct measurements were made with a duration of 300–500 minutes (no more than 5 % statistical error).
Keywords: tritium; water radioactivity; measurement methods; average value of specific activity of tritium; dose loads